Brief report on the Third International Conference on Applications of Optics and Photonics, AOP2017 - Costa, Manuel F. M. (2017)
Celebrating Optics and Photonics and its outstanding positive impact in the world and in our everyday life, largely resulting from the current remarkable success and fast sustainable development in O&P research, the Portuguese Society for Optics and Photonics, SPOF - Sociedade Portuguesa para a Investigação e Desenvolvimento em Óptica e Fotónica, successfully organised its third triennial international conference on Applications of Optics and Photonics, May 8 to 12, at the University of Algarve in the lovely city of Faro, Portugal.